The association of marital status with kidney cancer surgery morbidity - a retrospective cohort study - Tang, Yuzhe; Valovska, Marie-Thérèse; Nolazco, José Ignacio; Yim, Kendrick; Chung, Benjamin Inbeh; Chang, Steven Lee (Frontiers in Oncology, 2023)
To better understand whether the marital status impacts 90-day postoperative outcomes following kidney cancer surgery.We performed a retrospective cohort study of adult patients undergoing elective partial or radical nephrectomy to manage kidney masses from 2003 to 2017 using the Premier Hospital Database, a national hospital discharge dataset. Multinomial logistic regression models controlling for a wide range of clinicodemographic, surgical, and hospital characteristics were used to assess an association between marital status and postoperative complications. The primary outcome was 90-day complications, including minor complications (Clavien grades 1-2), non-fatal major complications (Clavien grades 3-4), and mortality (Clavien grade 5). Secondary outcomes included patient disposition and readmission rates.The study cohort comprised 106,752 patients, of which 61,188 (57.32%) were married. The overall incidence of minor complications, major complications, and death was 24.04%, 6.00%, and 0.71%, respectively. Marriage was associated with a significantly lower incidence of minor (RR 0.97; 95% CI: 0.94-0.99) complications following open or radical nephrectomy and major complications (RR 0.89; 95% CI: 0.84-0.95) for all surgical types and approaches (Figure 1).There was no association between marital status and mortality (RR 0.94; 95% CI: 0.81-1.10).2 Marriage is associated with a significant reduction in major complications following kidney cancer surgery, likely because it is associated with greater social support, which is beneficial in the postoperative phase of care. Marital status and social support may play a role in the preoperative decision-making process and counseling for patients considering kidney cancer surgery.